Multiculturalism as Multimodal Communication A Semiotic Perspective - Olteanu, Alin (Numanities - Arts and Humanities in Progress,, 2019)
This highly readable book develops a numanistic, and specifically semiotic approach to multiculturalism. It reveals how semiotics provides fresh and valuable insights into multiculturalism: in contrast to the binary logic of dualistic philosophy, semiotic logic does not understand the value of truth in rigid terms of 'true' or 'false', 'right' or 'wrong' only. The value of truth resides in meaning, which is a dynamic, evolutionary phenomenon, rooted, nevertheless, in factuality. Drawing on recent developments in biosemiotics, the book presents a theoretical approach to multiculturalism, regarding the lives of people living in multicultural environments. Rather than analyzing political or economic phenomena, it offers a semiotic analysis of multiculturalism and discusses its educational implications. It also invites readers to regard learning as a phenomenon of ecological sign growth and to understand multiculturalism along the same lines. As such, it brings together the life and social sciences and the humanities in a unified perspective, in an approach fitting postmodernism. Developing a postmodern philosophy for contemporary non-experts, which allows distancing from political discourse in favor of a posthumanistic stand, where altruism is seen as an opportunity, not a threat, this book appeals to a wide readership, from scholars seeking state-of-the-art theories to general readers looking for a thought-provoking and enlightening read.